2009
DOI: 10.1002/hyp.7382
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling groundwater chemistry in an agricultural area with complex topographic and land use patterns in mid‐western South Korea

Abstract: Abstract:Shallow and bedrock groundwater from granitic aquifers were investigated for the hydrogeochemistry of major and minor constituents in an agricultural area. Nitrate concentrations were observed up to 49 mg/l as NO 3 -N, with 22% of samples exceeding the drinking water standard, which could pose a significant threat because most residents rely on groundwater as their drinking water source. Principal component analysis revealed three principal components (PCs): (1) nitrate contamination, contributed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The concentrations of major cations were also the highest in Group 2 except for Mg, which was the second highest (Figure 5b-d). Although Mg concentrations were not the highest in Group 2, they were still higher than those reported in samples with high anthropogenic pollution in other areas in Chungnam province [14]. F and HCO concentrations were the lowest and the second lowest, respectively (Figure 5e,f).…”
Section: Hierarchical Cluster Analysismentioning
confidence: 67%
See 2 more Smart Citations
“…The concentrations of major cations were also the highest in Group 2 except for Mg, which was the second highest (Figure 5b-d). Although Mg concentrations were not the highest in Group 2, they were still higher than those reported in samples with high anthropogenic pollution in other areas in Chungnam province [14]. F and HCO concentrations were the lowest and the second lowest, respectively (Figure 5e,f).…”
Section: Hierarchical Cluster Analysismentioning
confidence: 67%
“…The results in Figure 2 indicate that groundwater mineralization in the study area was driven by two factors, NO − 3 contamination and natural process of weathering [14]. Major cations showed high concentrations in many of the samples, which may be introduced to groundwater either through natural water-rock interaction or from contamination sources from the ground surface.…”
Section: Hydrogeochemical Processes Affecting Groundwater Chemistrymentioning
confidence: 94%
See 1 more Smart Citation
“…Chae et al (2004) found that thick silt layers with low permeability effectively limit nitrate levels in groundwater, and create favorable conditions for denitrification. The low nitrate loading of paddy fields was also noted by Koh et al (2009). Temporal variations in nitrate levels can be explained in terms of seasonally different patterns of rainfall and irrigation.…”
Section: Processes Controlling Temporal Variation In Nitrate Concentrmentioning
confidence: 85%
“…pH, HCO 3 , and F showed higher rankings in the BL group while DO, NO 3 -N, and Cl did in the EL group. The relationship between land use and nitrate concentrations in an agricultural area with crystalline bedrock was studied by Koh et al (2009) in Nonsan, South Korea. The study indicated that the nitrate concentration was strongly affected by land use and topography, in terms of sources and attenuation processes.…”
Section: Hydrogeochemical Characteristicsmentioning
confidence: 99%